Guiding Attention in a Virtual Reality Theater: A case study of the Virtual Reality Performance Symmetry - Gallist, Nils; Hagler, Juergen; Lankes, Michael (Proceedings of CAGA24: The Conference of AG Animation 2024, 2025)
With comparatively new technologies such as Virtual Reality (VR), Augmented Reality (AR), Mixed Reality (MR), and Spatial Computing, the range of interaction possibilities for theatrical performances is expanding considerably. While classical user interfaces are based on predefined visual compositions, VR applications can create highly dynamic scenarios in which the impact of established attention-guiding techniques has an uncertain effect on the user. Users often have a great deal of freedom of movement, which can make established attention-guiding approaches less effective. This study examines the challenges and solutions associated with attention-guiding in VR environments, particularly in the context of digital theater productions. The study focuses on the development and implementation of attention-guiding techniques for the VR performance Symmetry. Combining expert interviews, systematic research, and practical implementation, this research aims to identify non-intrusive and intuitive methods to effectively guide users’ attention. The results highlight the importance of visual cues, color saturation, and salience modulation to enhance user engagement and immersion while addressing the challenges posed by emerging technologies in the theatrical space.